COMPUTERIZED BOOKKEEPING DESIGN IN SYSTEM ADMINISTRATION BRANCH IN. COMMERCIAL BANKS SERVITIA - Rustan Sutedja; Drs. H. Soetirto Sadikin MA Drs. H. Soetirto Sadikin MA (Jurnal Sistem Informasi, 1992)
PT. BANK UMU Servitia a company which is engaged in banking, each branchoffice / Capem Admionistrasi Bookkeeping obliged to make statements for purposesof the Head Office or branch itself. But problems often arise in making these reportsat the branch.